2009
DOI: 10.1021/bi801916j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dehaloperoxidase Compound ES and Its Reactivity with Trihalophenols

Abstract: Dehaloperoxidase (DHP), the oxygen transport hemoglobin from the terebellid polychaete Amphitrite ornata, is the first globin identified to possess a biologically relevant peroxidase activity. DHP has been shown to oxidize trihalophenols to dihaloquinones in a dehalogenation reaction that uses hydrogen peroxide as a substrate. Herein, we demonstrate that the first detectable intermediate following the addition of hydrogen peroxide to ferric DHP contains both a ferryl heme and a tyrosyl radical, analogous to Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
165
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(187 citation statements)
references
References 42 publications
21
165
1
Order By: Relevance
“…We have recently shown that compound I is not observed in DHP A and that compound ES is rapidly formed. 12 We recently confirmed similar observations for DHP B. 9 Both compound I and compound ES consist of a Fe(IV)dO species and a cation radical.…”
Section: Dhp a Protein Growthsupporting
confidence: 75%
See 2 more Smart Citations
“…We have recently shown that compound I is not observed in DHP A and that compound ES is rapidly formed. 12 We recently confirmed similar observations for DHP B. 9 Both compound I and compound ES consist of a Fe(IV)dO species and a cation radical.…”
Section: Dhp a Protein Growthsupporting
confidence: 75%
“…We have further shown that the radical is located on one of the five tyrosines in DHP A. 12 Since compound ES formation appears to be rapid in DHP, we present the peroxidase rate scheme with a compound ES intermediate. The compound ES is reduced in two one-electron steps by a substrate, XAOH, which is 2,4,6-TCP in the present study.…”
Section: Dhp a Protein Growthmentioning
confidence: 96%
See 1 more Smart Citation
“…Upon the substitution of this tyrosine with asparagine in DHP B this hydrogen bond is lost, but Asn34 is capable of forming a much stronger hydrogen bond to the carbonyl O atom of Glu31 as well as a couple of very weak ionic interactions with the side chains of Glu31 and Asn96. Thus, since Tyr34 has been implicated as one possible site of radical formation in DHP B Compound ES (Feducia et al, 2009), its replacement by a redox-inactive asparagine residue may affect either the site of radical formation in DHP B Compound ES or may alter the pathway for the migration of this radical out of the active site. Furthermore, the substitution-induced differences in the distal pocket of DHP B versus DHP A directly affect both the conformations of critical is the ith measurement of I(hkl) and hI(hkl)i is the weighted mean of all measurements of I(hkl).…”
Section: Protein Purification Characterization and Crystallizationmentioning
confidence: 99%
“…However, two isoforms of dehaloperoxidase, termed DHP A and DHP B, occur in A. ornata and are encoded by two separate genes (dhpA and dhpB; Han et al, 2001). Both have been shown to catalyze the oxidative dehalogenation of 2,4,6-trihalogenated phenols to the corresponding 2,6-dihalo-1,4-benzoquinones in the presence of hydrogen peroxide (Feducia et al, 2009;D'Antonio et al, 2010). Although they share 96% sequence identity (DHP B differs from DHP A at five positions: I9L, R32K, Y34N, N81S and S91G), significant spectroscopic and mechanistic differences between dehaloperoxidase isoenzymes A and B have recently been elucidated (D'Antonio et al, 2010).…”
Section: Introductionmentioning
confidence: 99%